2022
DOI: 10.3390/cancers14174116
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Oral Microbiome in the Development, Detection, and Management of Head and Neck Squamous Cell Cancers

Abstract: The role of the microbiome in the development and propagation of head and neck squamous cell cancer (HNSCC) is largely unknown and the surrounding knowledge lags behind what has been discovered related to the microbiome and other malignancies. In this review, the authors performed a structured analysis of the available literature from several databases. The authors discuss the merits and detriments of several studies discussing the microbiome of the structures of the aerodigestive system throughout the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 180 publications
0
15
0
Order By: Relevance
“…The potential role of oral microbiota on head and neck squamous cell carcinoma (HNSCC) incidence and management has also been studied [ 34 ]. Hayes et al showed an association between greater oral abundance of commensal Corynebacterium and Kingella spp.…”
Section: The Microbiota and The Immune Systemmentioning
confidence: 99%
“…The potential role of oral microbiota on head and neck squamous cell carcinoma (HNSCC) incidence and management has also been studied [ 34 ]. Hayes et al showed an association between greater oral abundance of commensal Corynebacterium and Kingella spp.…”
Section: The Microbiota and The Immune Systemmentioning
confidence: 99%
“…In general, there was an enrichment in Fusobacterium within cancer tissue samples that correlated with an inflammatory phenotype [34]. However, inconsistencies are observed for microbes such as Streptococcus, Actinomyces and Prevotella, meaning that it is necessary to identify a consensus microbiota signature for HNSC [27,31,32,35,36]. Previous systematic reviews have tried to identify and describe the dysbiosis in HNSC using processed [37][38][39][40][41][42][43] or re-analysed [44] data from studies containing heterogeneous HNSC sample types such as saliva, swab, oral rinse and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Samples studied include tissues, swabs and oral fluids (saliva or oral rinse) from cancer and healthy patients. Specifically for HNSC tissue microbiota analysis, samples included cancer, cancer-adjacent (approximately >5 mm away from the tumour), contralateral and healthy donor tissue samples [26][27][28]. Most bacteria identified in HNSC are oral commensal bacteria from the genera Streptococcus, Rothia, Fusobacterium, Haemophilus and Prevotella [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the oral microbiome associated with cancer therapy may result in dysbiosis, which is an imbalanced state in the local oral microenvironment. Oral dysbiosis is characterized by an overgrowth of pathogenic and opportunistic microorganisms and a reduced abundance of commensal microorganisms 5 . These changes may exacerbate therapy‐induced OM through several mechanisms, including the promotion of local inflammation due to the overgrowth of certain bacteria or fungal species, weakening of the oral mucosal barrier, and impacting the immune response of the host 5 …”
Section: Introductionmentioning
confidence: 99%
“…5 These changes may exacerbate therapy-induced OM through several mechanisms, including the promotion of local inflammation due to the overgrowth of certain bacteria or fungal species, weakening of the oral mucosal barrier, and impacting the immune response of the host. 5 However, there is still a lack of systematically reviewed evidence characterizing oral dysbiosis associated to OM. Thus, this review aims to characterize the oral microbiome changes associated with OM in patients undergoing cancer treatment.…”
Section: Introductionmentioning
confidence: 99%